Zika virus: Where to from here? - Muchaal, PK (Can Commun Dis Rep, 2018)
After the waves of reported cases of infection with Zika virus swept across the Americas in 2015–16, the overall transmission of the virus in the Western Hemisphere declined in 2017. Between June 8 and August 31, 2017, only 16 new cases of Zika virus infection, all travel-related, were reported in Canada. This represents an 88% reduction in the cases recorded during the same time frame in 2016. Herd immunity undoubtedly constrains the transmission of the virus in endemic regions. However, while most countries in the Americas are no longer observing continuous transmission in the form of sustained increases over time, some areas are experiencing a notable resurgence. Zika virus, in the wake of dengue, West Nile and chikungunya, has become one of the globalized emerging infections—proliferating beyond previously restricted geographic zones. Zika virus is no longer deemed a global health crisis but the virus’ unique potential to cause neurological anomalies in fetuses remains a significant concern.